Examining the spatial distribution of crime by victim characteristics - Jennings, Wesley G. (Deviant behavior, 2021)
It is well known that victims do not consistently report crimes. More problematically, victims in disadvantaged neighborhoods with high percentages of minority residents are not likely to report at high rates. Crime mapping is often considered at an aggregate level; however, the present study examines crime from a victim-perspective to better understand how crime is distributed by victim characteristics. Results reveal interesting similarities and differences in the geographical distribution of crime when disaggregated by victim race. Implications and directions for future research are also discussed.